Job satisfaction among academic staff: A case study in the public university in Malaysia - Noorshella Che Nawi; Mohammad Ismail; Nursalihah Ahmad Raston; Azila Jaini; Mohd Asrul Hery Ibrahim; Azwan Abdullah; Zaminor Zamzamir@Zamzamin (Medwell Journals, 2017)
The study reported here perceivedatmosphere, research, teaching and learning, benefits and governance as factors contributing towards job satisfaction among the academic staffs of public universities in Malaysia under the premises of existing literature. This study adopted a cross-sectional design and quantitative data was collected from the 71 selected respondents working as academic staff in a public university within Peninsular Malaysia. Findings of this study revealed that teaching and learning, benefits and governance has significant effect on the job satisfaction of academicians in public universities of Malaysia. Particularly benefits and governance have been found to have a highly significant effect on the job satisfaction level of academics. In order to enhancejob satisfaction among the academics, the packages and policies of universities should therefore focus on improving benefits for the academicians and imply more liberalizing governance upon them.